2019
DOI: 10.3389/fpsyg.2019.02616
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Moderators of Acute Aerobic Exercise on Subsequent Interference Control: A Systematic Review and Meta-Analysis

Abstract: Background: Acute aerobic exercise leads to positive physiological adaptations within the central nervous system. These findings inspired research on potential cognitive benefits following acute aerobic exercise. The effects of acute aerobic exercise on subsequent cognitive performance, by far, have been the most researched for interference control, a subcomponent of executive function. The results of primary studies on the effects of acute aerobic exercise on subsequent interference control performance are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 103 publications
5
60
1
Order By: Relevance
“…Furthermore, the results of Li et al [106] and Mehren et al [101] suggest that changes in functional brain activation patterns depend on (i) the cardiorespiratory fitness level, (ii) the exercise protocol, and (iii) sex. Although the number of fMRI studies in this area is limited, the moderating roles of (i) cardiorespiratory fitness levels [30], (ii) exercise intensity [30,200], and (iii) sex [30] are in accordance with the literature in summarizing the effects of acute physical exercise on behavioral performance. Thus, there is good reason to assume that investigations using fMRI can help to elucidate the effects of the mentioned moderators on neural correlates.…”
Section: Resultssupporting
confidence: 53%
“…Furthermore, the results of Li et al [106] and Mehren et al [101] suggest that changes in functional brain activation patterns depend on (i) the cardiorespiratory fitness level, (ii) the exercise protocol, and (iii) sex. Although the number of fMRI studies in this area is limited, the moderating roles of (i) cardiorespiratory fitness levels [30], (ii) exercise intensity [30,200], and (iii) sex [30] are in accordance with the literature in summarizing the effects of acute physical exercise on behavioral performance. Thus, there is good reason to assume that investigations using fMRI can help to elucidate the effects of the mentioned moderators on neural correlates.…”
Section: Resultssupporting
confidence: 53%
“…A recent systematic review ( 18 ) on the cognitive effects of acute aerobic exercise showed that short bouts of aerobic exercise improve interference control—a subcomponent of inhibition and closely linked to dual-task performance ( 19 ). Moderator analyses further revealed that effects were larger in age groups with poorer interference control such as preadolescent children and older adults.…”
Section: Introductionmentioning
confidence: 99%
“…During childhood and adolescence, the behavioral and neural plasticity is particularly high, and the brain regions serving EF (i.e., the prefrontal lobe) are specifically sensitive to environmental influences (Bull et al, 2011). Furthermore, the findings on empirical studies and meta-analysis show converging evidence of stronger training and transfer effects on children than on adults (Karbach and Kray, 2009;Karbach and Unger, 2014;Zhao et al, 2016;Oberste et al, 2019). Therefore, we included children as the target age group to investigate the characteristics of EF training effect.…”
Section: Introductionmentioning
confidence: 99%